PERANCANGAN UI & UX APLIKASI PERSEDIAAN BAHAN BAKU UNTUK PRODUKSI PADA PT. INDOMAS PRIMA SEJATI: Pendahuluan, Tinjauan Pustaka, Metode Penelitian, Pembahasan, Kesimpulan dan Penutup - Ira Damayanti; Ismail (Informatics and Computer Engineering Journal, 2024)
Indomas Prima Sejati is a company operating in the manufacturing sector. Management of raw material inventory data at PT. Indomas Prima Sejati is currently still doing it manually in preparing the latest stock reports. This manual approach is less effective and efficient because it has the potential to cause errors in recording and takes a long time to compile inventory reports. Raw materials are a number of materials used in the production process for resale. Therefore, raw material inventory management is very important for company operations because it has an impact on production efficiency, fulfilling consumer demand, and operational costs. In the midst of advances in the current digital era, the use of technology can help overcome this problem. To increase efficiency in managing raw materials, an inventory application design was designed that uses the design thinking method to create a User Interface (UI) and User Experience (UX) prototype. This application aims to simplify and increase the effectiveness of managing raw materials in the production process PT. Indomas Prima Sejati. This research chooses the design thinking method because its approach focuses on users, so that it can provide solutions that suit their needs. The design thinking process consists of five stages: empathize, define, ideate, prototype, and testing. In the testing stage, the researcher uses the Single Ease Question (SEA) approach to the some respondents to measure the level of ease of design solutions that have been made. Single Ease Question (SEA) is a testing technique by giving one question to respondents related to the task being tested. The application testing was successful in terms of ease of design solutions from respondents by getting an average score of 4,5 for application creation requests, then the prototype test results got an average score of 8.4 which means that the features made are easy to understand and understand.